Anticancer therapy and apoptosis imaging - Yalcin, T.J.; Haimovitz-Friedman, A.; Verheij, M. (Experimental Oncology, 2012)
Early response prediction is considered an essential tool to obtain a more customized anticancer treatment because it allows for the identification of patients who will benefit most from a particular therapy and prevents the exposure of those patients to toxic, non-effective regimens. Recent discoveries of novel markers in functional imaging have created exciting opportunities for in vivo visualization and quantification of cell death. This review will focus on in vivo apoptosis imaging with various radiotracers as predictive tools for tumor response after anticancer therapy. Particular focus will be on annexin V imaging, a technique with the largest clinical experience to date. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.